Solve the given parametric equation

  • Thread starter chwala
  • Start date
  • Tags
    Parametric
In summary, the conversation discusses two approaches to finding the solution for part (a) of a mathematical problem, using equations and the cartesian equation. Part (b) is then solved using differentiation and the length ratio of PA to PB is found to be 2:p^-2.
  • #1
chwala
Gold Member
2,766
395
Homework Statement
See attached
Relevant Equations
differentiation
1654948836414.png

For part (a) i have two approaches;
We can have,

##\dfrac{dy}{dx}=\dfrac{dy}{dt}\cdot\dfrac{dt}{dx}##
##\dfrac{dy}{dx}=-\dfrac{2}{x^2}##
##\dfrac{dy}{dx}\left[x=\frac{1}{p}\right]=-2p^2##

Therefore,
##p(y-2p)=-2p^3x+2p^2##
##py=-2p^3x+4p^2##
##y=-2p^2x+4p##The other approach to this is;
since ##y=2t## and ##x=\dfrac{1}{t}## then we shall have the cartesian equation, ##xy=2.## It follows that
##y+x\dfrac{dy}{dx}=0##
##\dfrac{dy}{dx}=-\dfrac{y}{x}=-2p^2##

The other steps shall follow as previously shown.

For part (b),
We have
##y=-2p^2x+4p##
at ##x## axis, ##y=0## therefore
##2p^2x=4p##
##px=2##
##x=\dfrac{2}{p}##
The co ordinates at ##A\left[\dfrac{2}{p},0\right]##
##PA=\sqrt{\left[\dfrac{2}{p}-\dfrac{1}{p}\right]^2+[2p-0]^2}=\dfrac{\sqrt{4p^4+1}}{p}##

Let the gradient of the normal be given by ##m##,
##-2p^2\cdot m=-1##
##m=\dfrac{1}{2p^2}##
therefore we shall have for ##PB##
##\dfrac{y-2p}{px-1}=\dfrac{1}{2p^2}##
##2p^3(y-2p)=px-1##
##-4p^4=px-1##
##x=\dfrac{1-4p^4}{p}##

The co ordinates at ##B\left[\dfrac{1-4p^4}{p},0\right]##

##PB=\sqrt{\left[\dfrac{1-4p^4}{p}-\dfrac{1}{p}\right]^2+[2p-0]^2}=\sqrt{16p^6+4p^2}=\sqrt{4p^2(4p^4+1)}=2p\cdot\sqrt{4p^4+1}##

Therefore, ##PA:PB=\dfrac{1}{p}:2p=1:2p^2##

Of course this was easy...i always like seeking different ways if any to solve this hence my posts...Cheers guys:cool:
 
Last edited:
  • Like
Likes Maarten Havinga and Delta2
Physics news on Phys.org
  • #2
I don't know if you can do something cunning using the fact that the curve is a conic section (hyperbola).
 
  • Informative
Likes Delta2
  • #3
I spotted one small typo, you have omitted a ##p## factor in the equation following the
chwala said:
Homework Statement:: See attached
Relevant Equations:: differentiation

therefore we shall have for PB
The correct should be $$\frac{p(y-2p)}{px-1}=\frac{1}{2p^2}$$. The rest of solution remains correct cause you bring back the p factor in the following lines.
 
  • Like
Likes chwala
  • #4
You can solve (b) by taking ##x'=dx/dt## and ##y'=dy/dt## at P. The length ratio of PA to PB will be ##|y'/x'|## due to ##(P,A,X)## being congruent to ##(B,A,P)##. This evaluates to 2 : ##p^{-2}## and multiply by ##p^2## to get the right answer! :-)
 
  • Like
Likes chwala

Similar threads

Back
Top